ELECTRONIC LIBRARY SYSTEM BASED ON QR- CODE TECHNOLOGY AND CREATE SOFTWARE AND HARDWARE SUPPLY - Yunusova Nargiza Baxodirovna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Annotation: This article is about QR code technology. How it works currently, there are opinions and comments on where this technology can be used and its effectiveness. Based on the QR code technology, the QR-bookland mobile application was developed, and the ease of use of this application is described in detail.